Friday

December 19, 2014

December 19, 2014

Posted by **Brian** on Saturday, March 10, 2012 at 2:49pm.

- Calculus -
**Anonymous**, Monday, March 12, 2012 at 12:16pmchange your x's to y's

y=1/4x-3

x=1/4y-3

x-3=1/4y

4(x-3)=y

you got it from there

**Answer this Question**

**Related Questions**

Calculus Help - The formula C =5/9(F − 32), where F ≥ −459.67...

math - The cost of producing q articles is given by the function C=f(q)=100+2q...

Pre-calculus - Given the following values for f(t): t : f(t) 3 : -7 6 : 6 9 : 19...

Algebra - The function f(x)=x 3 +1 4 x−1 4 is a monotonically increasing ...

Calculus - Given f(x)=−2x^3 -3x + 1, the value of the derivative of the ...

calculus - Give a possible formula for the illustrated function using a vertical...

pre calculus - Find the inverse of the function below. Graph the function below ...

Algebra(1st one was typo) - The function f(x)=x^3 +1/4 x −1^4 is a ...

calculus - f(x) = (x+2)/(x+6) What is f^(-1)(-6)? (what is f inverse of -6) I ...

Pre-Calculus - Find the inverse function for the function f(x)=2^(x)+1/2^(x)-1 ...